Critical Factors of Knowledge Management and the Delivery of Information Services in Academic Libraries in Yemen - Hanan Hamood Saleh; Noor Hasrul Nizan (Journal of Computing Technologies and Creative Content, 2022)
This paper investigates the knowledge management perception of the Yemeni academic libraries by librarians and the factors that contribute to improve the delivery of information services. As the scope of the knowledge management is wide, this study was confined only to the knowledge creation and sharing processes of knowledge management. Data were collected from 289 librarians of twenty-nine libraries in the Yemeni universities using self-administered questionnaires and were analyzed using the Social Sciences Statistical Package (SPSS) and Structural Equation Modeling (SEM). The study found that the positive effective of knowledge sharing on the improvement in the delivery of information services indicates a good atmosphere of confidence and mutual relationship. Also, the results showed that the positive effect between knowledge creation process and knowledge sharing process on librarians’ attitude indicates their concern of their status and image. Furthermore, the study found that the high level of confidence of librarians that their expertise will only be used properly and for the benefit of each other. It also indicates that they can depend on each other when they are looking for new knowledge or need help. In terms of the theoretical contribution, the study integrates both knowledge management processes and organizational climate perspectives to develop a theoretical model that explain the concept of the improvement in the delivery of information services. From the practical contribution perspective, fills the gab in literature on knowledge management process particularly in academic institution in Yemen.